EMULGEL EMERGENT SYSTEMS: AT A GLANCE FOR TOPICAL DRUG DELIVERY - VISHWAKARMA, GIRJESH; SINGH PANWAR, AAKASH (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Emulgels have been emerged both in cosmetics and pharmaceutical preparations. When gel and emulsion are used in the combined form, they are referred to as Emulgel. Emulgel is a promising drug delivery system for the delivery of hydrophobic drugs. Emulgel is an emulsion that is gelled by mixing it with gelling agents. Many advantages of gels have the major limitation of delivery of hydrophobic drugs. Hence, the emulsion-based approach is being used to overcome this limitation. Emulgel is an interesting topical drug delivery system as it has a dual release control system, i.e., gel and emulsion. The use of gels and emulsions as combined dosage form results in the formation of emulgel showing dual release. With this approach, polymers with enhanced effect in release patterns have emerged, providing sustained and controlled release. They are generally applied for antiseptics, antifungal agents, skin emollients, and protectants. The activity of topical preparation confides in various factors such as drug solubility, lipophilicity, contact time to the skin, and permeability. Emulgels have numerous advantages in dermatology, such as being thixotropic, greaseless, easily spreadable, easily removable, emollient, nonstaining, long shelf life, bio-friendly, transparent and pleasing appearance. Emulgel is being used to deliver analgesics, anti-inflammatory, antifungal, anti-acne drugs, and various cosmetic formulations with a wide range to explore.